1995
DOI: 10.1128/aem.61.7.2548-2553.1995
|View full text |Cite
|
Sign up to set email alerts
|

Denitration of glycerol trinitrate by resting cells and cell extracts of Bacillus thuringiensis/cereus and Enterobacter agglomerans

Abstract: A number of microorganisms were selected from soil and sediment samples which were known to have been previously exposed to nitrate ester contaminants. The two most effective bacteria for transforming glycerol trinitrate (GTN) were identified as Bacillus thuringiensis/cereus and Enterobacter agglomerans. For both isolates, denitration activities were expressed constitutively and GTN was not required for induction. Dialysis of cell extracts from both isolates did not affect denitration, which indicates that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 15 publications
3
25
2
Order By: Relevance
“…The removal of nitrite after generation was probably the result of autotrophic NO 2 Ϫ -N oxidation. A mechanism involving hydrolytic cleavage of nitrate esters followed by reduction of nitrate to nitrite has been proposed before (Meng et al, 1995). The data in this study do not corroborate such a two-step enzymatic process for GTN degradation but suggest the direct denitration of GTN with the release of nitrite.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…The removal of nitrite after generation was probably the result of autotrophic NO 2 Ϫ -N oxidation. A mechanism involving hydrolytic cleavage of nitrate esters followed by reduction of nitrate to nitrite has been proposed before (Meng et al, 1995). The data in this study do not corroborate such a two-step enzymatic process for GTN degradation but suggest the direct denitration of GTN with the release of nitrite.…”
Section: Discussioncontrasting
confidence: 88%
“…Because GDN denitration was the rate-limiting step in GTN conversion to glycerol, it was not possible to compare relative rates of GTN and GMN denitration. Some authors working with whole cells or isolated enzymes inferred that GDN denitration was nonconcomitant with GTN denitration (Meng et al, 1995, andWhite et al, 1996), whereas concomitant denitration of GTN and GDN was observed with isolated reductases (Blehert et al, 1997) and aerobic enrichment cultures (Accashian et al, 1998). In the current work, all nitrate esters were denitrated simultaneously and concomitantly because GDN removal occurred while GTN was still present and GMN isomers were never detected (Figure 4).…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…However, the degradation was not complete, as GDN and GMN were still present in the spent medium (19). Recently, Meng et al (10) reported that GTN can be completely denitrated during a long-term incubation with cell extracts of either Bacillus thuringiensis plus Bacillus cereus or Enterobacter agglomerans. Although the method of Meng et al appears to effectively degrade GTN, it must be pointed out that B. cereus and E. agglomerans are mammalian pathogens whereas B. thuringiensis is an insect pathogen (6,12,16).…”
mentioning
confidence: 99%